The Influence of Content Marketing, Online Customer Review, and Product Quality on the Purchase Decision of Mossdoom Bags, Faculty of Economics and Business, Universitas Nusantara PGRI Kediri - Uppalavana, Metta; muslih, basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : : This study was conducted to determine the influence of content marketing, online customer reviews, and product quality on purchase decisions either or simultaneously Design/Methode/Approach: This study uses a quantitative approach with a causal method. Using nonprobability sampling samples with a purposive sampling approach. The data collection technique used in this study uses a questionnaire that is distributed to the respondents. Data analysis techniques using multiple linear regression analysis models using statistical analysis include validity and reliability tests, classical assumption tests, multiple linear regression tests, determination coefficient tests and hypothesis tests. Research Finding : The results of this study show that content marketing and online customer reviews and product quality have a significant effect. Theoretical contribution/Originality: this study can be a reference for future researchers regarding the influence of marketing content, online customer reviews, product quality on the purchase decision of Mossdoom bags. Practitionel/Policy implication: This research is expected to help mossdoom in developing the right marketing strategy by optimizing the use of Content Marketing, Online Customer Review, and product quality to improve purchase decisions Research limitation : : this study focuses on determining the influence of content marketing, online customer reviews, and product quality on the purchase decision of mossdoom bags among students of the Faculty of Economics and Business UNP Kediri.